ANALISIS KARAKTERISTIK DAN FORMULASI RAWA DENGAN PENDEKATAN VARIABEL HIDROLOGI RAWA - Nilna Amal (Universitas Lambung Mangkurat, 2021)
The characteristics of wetlands can be recognized through their hydrological and ecological conditions. The hydrology of a wetland determines whether it can function initially or change. Research on the hydrology of wetlands can start from applying an appropriate water balance and a runoff generation formula for a wetland. Hydrological analysis of wetlands, including peatlands as part of watersheds, requires proper research according to the circumstances. A water balance formula calculating the equilibrium between rainfall, evapotranspiration, surface water, and groundwater is essential for recognizing wetland conditions. Analysis of the watershed flow where the wetland is located can use the rational formulas and the unit hydrograph methods of generated flow that consider suitability for the wetland conditions. This analysis is carried out by calculating the influence of variables on the wetland; rainfall, surface flow, and water detention. Other variables related to soil properties have an influential aspect in determining flow generation. The overall variables effect is reflected in the changes in the downstream flow hydrograph of a watershed. It mainly seems in the recession curve of the flood hydrograph. The peak of the flow decreases in order to wetland presence. This change is a composite of the upstream flow alteration and wetland storage influence. The influence of wetland areas is also found in flood volume, which shows a proportional relationship, namely that the increase in wide wetland areas affects the decrease in flood volume.